ANALISIS KESULITAN BELAJAR SISWA PADA MATERI TAJWID DAN UPAYA GURU PAI DALAM MENGATASINYA DI KELAS X SMA NEGERI 16 TEBO - Pratama, Prandika; Sriani; Mabruri; Baili; Andryadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2022)
Tajwid instruction in senior high schools often presents a critical learning point due to its dual nature combining theoretical rules and recitation practice. This study aimed to analyze the types and levels of students’ learning difficulties in tajwid and map PAI teachers’ pedagogical efforts to overcome them. A descriptive quantitative-qualitative design was implemented at SMA Negeri 16 Tebo involving 124 tenth-grade students and three PAI teachers. Instruments included a tajwid diagnostic test (expert-validated CVI=0.88; α=0.84), pronunciation error observation sheets, semi-structured interviews, and lesson plan/remedial documentation. Test results showed 67.7% of students fell into moderate–high difficulty categories, with dominant error patterns in nun mati/tanwin rules (72.4%), mad (68.1%), and qalqalah (61.3%). Cause analysis revealed limited individual practice, regional accent interference, and scarce audio-visual media. PAI teachers responded through diagnostic-formative strategies, chunking-based differentiated instruction, interactive tajwid applications, and peer coaching systems. Discussion confirms that intervention effectiveness depends on alignment between precise difficulty identification, structured pronunciation scaffolding, and immediate corrective feedback. It is concluded that tajwid learning difficulties are multidimensional and require a pedagogical approach integrating precision diagnosis, guided practice, and supportive technology. The study recommends developing error-based remedial modules, teacher training in digital pronunciation assessment, and integrating routine tajwid practice into school culture.